Clinical Validation of a Commercial LAMP Test for Ruling out Malaria in Returning Travelers: A Prospective Diagnostic Trial. (12th October 2018) - Cheaveau, James; Nguyen, Hong; Chow, Barbara; Marasinghe, Dewdunee; Mohon, Abu Naser; Yuan, Hong; Viana, Gisele; van Schalkwyk, Donelly; Church, Deirdre; Chan, Wilson; Pillai, Dylan R
Abstract: The mainstay of malaria diagnosis relies on rapid diagnostic tests (RDTs) and microscopy, both of which lack analytical sensitivity. This leads to repeat testing to rule out malaria. A prospective diagnostic trial of the Meridian illumigene Malaria assay (loop-mediated isothermal amplification [LAMP]) was conducted comparing it with reference microscopy and RDTs (BinaxNOW Malaria) in returning travelers between June 2017 and January 2018. Returning travelers with signs and symptoms of malaria were enrolled in the study. RDTs, microscopy, and LAMP assays were performed simultaneously. A total of 298 patients (50.7% male; mean age, 32.5 years) were enrolled, most visiting friends and relatives (43.3%), presenting with fever (88.9%), not taking prophylaxis (82.9%), and treated as outpatients (84.1%). In the prospective arm (n = 348), LAMP had a sensitivity of 98.1% (95% confidence interval [CI], 90.0%–100%) and a specificity of 97.6% (95% CI, 95.2%–99.1%) vs microscopy. After discrepant resolution with real-time polymerase chain reaction, LAMP had a sensitivity of 100% (95% CI, 93.7%–100%) and a specificity of 100% (95% CI, 98.7%–100%) vs microscopy. After discrepant resolution, RDTs had a sensitivity of 83.3% (95% CI, 58.6%–96.4%) and a specificity of 96.2% (95% CI, 93.2%–98.1%) vs microscopy. When including retrospective specimens (n = 377), LAMP had a sensitivity of 98.8% (95% CI, 93.2%–100%) and a specificity of 97.6% (95% CI, 95.2%–99.1%) vs microscopy, and after discrepant resolution of this set, LAMP had a sensitivity of 100% (95% CI, 95.8%–100%) and a specificity of 100% (95% CI, 98.7%–100%). A cost-benefit analysis of reagents and labor suggests savings of up to USD13 per specimen using a novel algorithm with LAMP screening.